Lay Beliefs And Responses Concerning Hypertension And Its Management In Two Culturally Distinct Groups - S.W.P. Mhlongo (South African Family Practice)
Objective: To determine quantitatively whether there are significant differences in lay beliefs about hypertension and its management between African- Caribbean (A.C.) living in the UK but born in the West Indian Caribbean Islands and white hypertensive patients in the UK.